Reference values for Doppler velocimetric indices from the fetal and placental ends of the umbilical artery in uncomplicated third trimester pregnancy - Paudel, S; Kayastha, P; Lohani, B; Gurung, G (Journal of Institute of Medicine Nepal, 2010)
Introduction: The purpose of this study was to establish new reference ranges for commonly used umbilical artery Doppler indices (Pulsatility Index, Resistance Index, and Systolic: Diastolic ratio) at standardized insonation sites in uncomplicated third trimester pregnancy. Methods: This was a prospective cross sectional study involving 101 singleton pregnancies between 30 and 37 weeks of gestation without any known risk factors. Umbilical artery indices were obtained from fetal end and placental end of the cord. Regression equations were used to construct reference ranges and percentile fitted Normograms were obtained for all the parameters. Paired t test was used to see the difference of different parameters at two different sites of the cord. Results: Among 101 singleton pregnancies between 30 and 37 weeks of gestation, 65 (64.35%) were primigravida and 36 (34.65%) were multigravida. Mean maternal age was 23.12years (range 16 to 35 years). Maximum number of pregnancies (18.81%) was at 34 weeks of gestation. The established Doppler indices showed a continuous reduction of all the measured indices as pregnancy increases (p<0.0001). Umbilical artery RI, PI and S: D ratio were higher in the fetal end of the cord than in the placental end (p><0.0001). Conclusions: Umbilical artery Doppler parameters vary significantly at different locations. We have established new reference ranges for the UA at fetal end and placental end of the cord which should be useful for the surveillance of fetuses with repeated observations.>